Tapping into collaborative skills and learning achievement: The effect of implementing the common knowledge construction model equipped with podcasts on chemical bonds topic - Sri Yamtinah; Nanik Dwi Nurhayati; Antuni Wiyarsi; Hayuni Retno Widarti; Ari Syahidul Shidiq; Fa'ari Salsabila (Pascasarjana Universitas Negeri Medan, 2024)
The impact of integrating the Common Knowledge Construction Model (CKCM) with Chemical Bonds-focused Podcasts on students' collaboration skills and cognitive learning achievements is investigated in this study. A quasi-experimental design was employed, with cluster random sampling to select the experimental (N=23) and control (N=30) classes from a private high school in Solo City. Descriptive and inferential analyses were conducted, employing the Mann-Whitney test for hypothesis testing. Results showed that the CKCM approach significantly enhanced collaboration skills (p < 0.001) and learning achievements (p = 0.014), indicating substantial educational benefits. In conclusion, integrating the CKCM with Chemical Bonds podcasts positively influenced students' collaboration skills and cognitive learning achievements. Moreover, this comprehensive model addressed conventional learning objectives and integrated elements of ethnoscience, providing students with a broader and more culturally contextualized understanding. The CKCM model, supplemented by podcasts, facilitated a dynamic learning environment that actively engaged students in knowledge construction. These findings advocate for integrating CKCM and podcasts into educational curricula, offering a scalable model for enhancing 21st-century skills.